Storing System in Improving Smoothness Goods Operations at Luwansa Beach Resort - Yohanes Bryan Jehabut; Agus Wahyudi (Eastasouth Institute, 2023)
The storage system is very important for every hotel because it can help improve the smooth operation of goods, so this study aims to analyze the string system implemented at the Luwansa Beach Resort Hotel in improving the smooth operation of the hotel. This type of research is qualitative research. The data collection techniques used observation and direct interviews with sources at Luwansa Beach Resort. The results of this study indicate that the storage and disposal of goods at the Luwansa Beach Resort Hotel has implemented a storage system and procedures using the first in first out (FIFO) system and the first expired first out (FEFO) system.